Lithium ion battery electrolyte and application thereof

By using fluorocarbonate solvents and lithium hexafluorophosphate in the lithium-ion battery electrolyte, combined with specific additives, a stable interface film is formed, which solves the problem of insufficient high-voltage resistance performance of the battery under high pressure, and significantly improves the battery's high-temperature cycle stability and performance.

CN119725759AActive Publication Date: 2025-03-28ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411960004.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-28
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing lithium-ion battery electrolyte has insufficient high-voltage resistance under high pressure, resulting in poor battery cycling stability, impedance growth and gas production at high temperatures.

Method used

A lithium-ion battery electrolyte is used, including fluorocarbonate solvents, lithium hexafluorophosphate and specific additives. Through the synergistic action of fluorocarbonate solvents and additives, a stable SEI and CEI film is formed to improve the high-pressure resistance of the electrolyte.

Benefits of technology

It significantly improves the battery's high-temperature cycle stability, suppresses the battery's impedance growth and high-temperature storage gas production, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725759A_ABST
    Figure CN119725759A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion battery electrolyte and application thereof, and the electrolyte at least comprises the following components: a fluorocarbonate solvent including 2, 2, 2-trifluoroethyl methyl carbonate and fluoroethylene carbonate; the lithium salt comprises a first lithium salt, and the first lithium salt comprises lithium hexafluorophosphate; the additive comprises a first additive, the structural general formula of the first additive is # imgabs0 #, R1 and R2 are independently selected from substituent groups with the carbon atom number of 1-6, the unsaturation degree of 0-4 and the heteroatom number of 0-3, and the heteroatom is selected from at least one of oxygen, nitrogen or sulfur. According to the lithium ion battery electrolyte and the application thereof provided by the invention, the high-voltage resistance of the electrolyte can be improved, the high-temperature cycling stability of the battery is remarkably improved, and the impedance increase and high-temperature storage gas production of the battery are inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of power batteries, and in particular to a lithium-ion battery electrolyte and applications thereof. Background Art

[0002] With the rapid development of the new energy vehicle market, the demand for high energy density lithium-ion batteries is becoming increasingly urgent. Among them, increasing the voltage of the battery as an intuitive and feasible method can increase the energy density of the battery. However, with the increase in battery voltage, higher requirements are placed on the high voltage resistance of the electrolyte. Among them, although the use of fluorinated solvents can improve the high voltage resistance of the electrolyte, it will corrode the solid electrolyte interface (Solid Electrolyte Interphase, SEI) membrane and the electrochemical interface (Chemical-Electrochemical Interface, CEI) membrane, resulting in interface damage and continuous side reactions, which ultimately manifests as a series of problems such as high temperature gas production, high temperature capacity loss and increased DC impedance of the battery, affecting the performance of the battery. Summary of the invention

[0003] The present invention proposes a lithium-ion battery electrolyte and its application. The lithium-ion battery electrolyte and its application provided by the present invention can improve the high-voltage resistance of the electrolyte, significantly enhance the high-temperature cycle stability of the battery, and inhibit the impedance growth of the battery and the gas production during high-temperature storage.

[0004] In order to solve the above technical problems, the present invention provides a lithium ion battery electrolyte, comprising at least the following components:

[0005] Fluorinated carbonate solvents, including 2,2,2-trifluoroethyl methyl carbonate and fluoroethylene carbonate;

[0006] a lithium salt comprising a first lithium salt comprising lithium hexafluorophosphate; and

[0007] The additive comprises a first additive, wherein the first additive has a general structural formula of:

[0008]

[0009] Wherein, R1 and R2 are each independently selected from a substituent having 1-6 carbon atoms, 0-4 unsaturation degrees and 0-3 heteroatoms, and the heteroatoms are selected from at least one of oxygen, nitrogen or sulfur.

[0010] In one embodiment of the present invention, the substituent is selected from at least one of an alkyl group, an alkenyl group, an alkynyl group, a carbonyl group, an ester group, an amino group or a heterocycle.

[0011] In one embodiment of the present invention, the first additive is selected from Compound 1, Compound 2 or At least one of compound 3.

[0012] In one embodiment of the present invention, the content of the first additive in the electrolyte is 0.05wt%-3wt%.

[0013] In one embodiment of the present invention, the content of the 2,2,2-trifluoroethyl methyl carbonate in the electrolyte is 10wt%-85wt%.

[0014] In one embodiment of the present invention, in the fluorocarbonate solvent, the mass ratio of the 2,2,2-trifluoroethyl methyl carbonate to the fluoroethylene carbonate is 9:1-7:3.

[0015] In one embodiment of the present invention, the lithium salt further includes a second lithium salt, and the second lithium salt is selected from at least one of lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide.

[0016] In one embodiment of the present invention, the content of the lithium salt in the electrolyte is 12wt%-20wt%, and the content of the first lithium salt in the electrolyte is 8wt%-20wt%.

[0017] The present invention also provides a lithium ion battery, comprising at least:

[0018] A positive electrode sheet, comprising a positive electrode active material, wherein the positive electrode active material has a structural formula of Li a Ni x Mn y O 4-z M z , wherein 0.9≤a≤1.1, 0.4≤x≤0.6, 1.4≤y≤1.6, 0≤z≤0.1, and M is selected from at least one of Cl, Br, I, S, Se, Te or F;

[0019] Negative electrode;

[0020] A separator, disposed between the positive electrode sheet and the negative electrode sheet; and

[0021] The electrolyte is selected from the above-mentioned lithium ion battery electrolyte.

[0022] The present invention also provides an electronic device, comprising the above-mentioned lithium-ion battery.

[0023] In summary, the present invention provides a lithium-ion battery electrolyte and its application, wherein the fluorocarbonate solvent can improve the high-voltage resistance of the electrolyte, making the electrolyte suitable for use in high-voltage system batteries. The fluorocarbonate solvent and the first additive work synergistically to form a stable SEI film at the contact interface between the negative electrode and the electrolyte, and a stable CEI film at the contact interface between the positive electrode and the electrolyte, thereby ensuring the stability of the electrode and electrolyte interface at high temperatures, thereby significantly improving the high-temperature cycle stability of the battery, and inhibiting the impedance growth of the battery and the gas production during high-temperature storage. DETAILED DESCRIPTION

[0024] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0025] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.

[0026] The technical scheme of the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0027] The present invention provides a lithium-ion battery electrolyte, comprising at least a fluorocarbonate solvent, a lithium salt and an additive, wherein the lithium salt comprises a first lithium salt, the first lithium salt comprises lithium hexafluorophosphate (LiPF6), the additive comprises a first additive, and the general structural formula of the first additive is: Wherein, R1 and R2 are each independently selected from a substituent having 1-6 carbon atoms, 0-4 unsaturation and 0-3 heteroatoms. Wherein, the heteroatom is, for example, selected from at least one of oxygen or sulfur. In the lithium ion battery electrolyte provided by the present invention, the fluorocarbonate solvent can improve the high voltage resistance of the electrolyte, making the electrolyte suitable for high voltage battery systems, and the fluorocarbonate solvent and the first additive act synergistically to form a stable SEI film at the contact interface between the negative electrode and the electrolyte, and a stable CEI film at the contact interface between the positive electrode and the electrolyte, thereby ensuring the stability of the interface between the electrode and the electrolyte at high temperature, thereby significantly improving the high temperature cycle stability of the battery, inhibiting impedance growth and high temperature storage gas production.

[0028] In one embodiment of the present invention, the fluorocarbonate solvent has good high-voltage stability, which can ensure the interfacial stability of the electrolyte on the positive electrode side. Moreover, since the fluorine atom has strong electron-withdrawing properties, the dissociation ability of the fluorocarbonate solvent to the lithium salt is reduced, which can promote the combination of lithium ions and anions, thereby forming a solvation structure dominated by salt anions, and the inorganic components in the interface phase increase, thereby increasing the stability of the interface phase. Specifically, in this embodiment, the fluorocarbonate solvent includes 2,2,2-trifluoroethyl methyl carbonate (Methyl2,2,2-trifluoroethyl ester, FEMC) and fluoroethylene carbonate (Fluoroethylene Carbonate, FEC), etc. Among them, the content of FEMC in the electrolyte is, for example, 10wt%-85wt%, and for example, 55wt%-75wt%, and the mass ratio of FEMC and FEC is, for example, 9:1-7:3. By controlling the mass ratio of FEMC and FEC, it is possible to reduce the battery impedance while avoiding the problem of increased interface byproducts between the electrode and the electrolyte caused by excessive FEC content, thereby improving the battery's high-temperature storage gas production rate and high-temperature cycle stability.

[0029] In one embodiment of the present invention, in the first additive, the substituents of R1 and R2 are independently selected from alkyl, alkenyl, alkynyl, carbonyl, ester, amino or heterocyclic rings. Specifically, in this embodiment, the first additive is selected from Compound 1, Compound 2 or At least one of compound 3, etc. Since many lithium salts decompose rapidly in the fluorocarbonate solvent system, the local temperature at the interface between the electrode and the electrolyte increases, and the presence of trace water in the electrolyte accelerates the hydrolysis of the first lithium salt, thereby increasing the acidity of the electrolyte. By introducing the first additive into the fluorocarbonate solvent, the first additive and the fluorocarbonate solvent act synergistically, especially under high temperature and high pressure, and can significantly inhibit the acid rise rate of the electrolyte, thereby reducing the damage of acidic substances such as HF to the interfacial phase, thereby significantly alleviating the decomposition of the electrolyte under high temperature and high pressure systems, thereby inhibiting the high temperature storage gas production and impedance growth of the battery, and improving the high temperature cycle stability of the battery.

[0031] In one embodiment of the present invention, the content of the first additive in the electrolyte is, for example, 0.05wt%-3wt%, and further, for example, 0.3wt%-1.5wt%. By controlling the content of the first additive, it is possible to suppress the high-temperature storage gas generation of the battery while avoiding the problem of increased interface byproducts between the electrode and the electrolyte caused by excessive content of the first additive, thereby improving the impedance and high-temperature cycle stability of the battery.

[0032] In one embodiment of the present invention, the additive further includes a second additive, which is, for example, a negative electrode film-forming additive, which is, for example, at least one selected from vinylene carbonate (VC), 1,3-propane sultone (PS) or vinyl sulfate (DTD), and the content of the second additive in the electrolyte is, for example, 0.1wt%-5wt%.

[0033] In one embodiment of the present invention, the content of the lithium salt in the electrolyte is, for example, 12 wt %-20 wt %, wherein the content of the first lithium salt in the electrolyte is, for example, 8 wt %-20 wt %.

[0034] In one embodiment of the present invention, the lithium salt further includes a second lithium salt, the second lithium salt is selected from at least one of lithium bis(fluorosulfonyl)imide (LiFSI) or lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and the content of the second lithium salt is, for example, 0.1wt%-3wt%. By introducing the second lithium salt, the conductivity of the electrolyte can be increased due to the second lithium salt having a stronger dissociation ability, thereby improving the impedance of the battery.

[0035] In one embodiment of the present invention, when preparing the electrolyte, in a glove box with a stable gas atmosphere such as argon, the battery-grade FEMC and FEC are mixed uniformly according to a mass ratio to obtain a fluorocarbonate mixed solvent, and the lithium salt and the additive are added to the fluorocarbonate mixed solvent and mixed uniformly to prepare a lithium-ion battery electrolyte. The moisture content in the glove box is, for example, less than 10 ppm.

[0036] The present invention also proposes a lithium-ion battery, and the lithium-ion battery includes a positive electrode plate, a separator, a negative electrode plate and an electrolyte. The separator is located between the positive electrode plate and the negative electrode plate to prevent a short circuit between the positive electrode plate and the negative electrode plate, so that lithium ions can pass through. The electrolyte is filled between the positive electrode plate, the separator and the negative electrode plate, and the electrolyte is the above-mentioned lithium-ion battery electrolyte, which plays a role in conducting ions. Among them, the lithium-ion battery is, for example, a primary battery or a secondary battery, and the secondary battery is, for example, a soft-pack battery, a hard-shell battery or a cylindrical battery, etc. The present invention does not specifically limit the type and type of the lithium-ion battery.

[0037] In one embodiment of the present invention, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer coated on at least one surface of the positive electrode current collector. The positive electrode current collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive electrode current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric.

[0038] In one embodiment of the present invention, the positive electrode active layer includes a positive electrode active material, a conductive agent, and a binder. The ratio of the positive electrode active material, the conductive agent, and the binder can be selected according to actual needs. In this embodiment, the positive electrode active material includes, for example, lithium nickel manganese oxide, and the chemical formula of lithium nickel manganese oxide is, for example, Li a Ni x Mn y O 4-z M z , wherein 0.90≤a≤1.10, 0.4≤x≤0.6, 1.4≤y≤1.6, 0≤z≤0.1, and M is selected from at least one of Cl, Br, I, S, Se, Te, or F. Further, in this embodiment, the surface of the positive electrode active material is provided with a coating layer, the material of the coating layer includes carbon, etc., and the mass of the coating layer is 1% to 3% of the mass of the positive electrode active material.

[0039] In one embodiment of the present invention, the conductive agent is, for example, selected from at least one of conductive carbon black (SuperP), acetylene black, carbon nanotubes or graphene, and the binder is, for example, selected from at least one of polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene or styrene butadiene rubber (SBR).

[0040] In one embodiment of the present invention, the positive electrode current collector is, for example, aluminum foil, the conductive agent is, for example, SuperP, the binder is, for example, PVDF, and the chemical formula of the positive electrode active material is, for example, Li 0.95 Ni 0.45 Mn 1.54 O4, and the surface of the positive electrode active material is provided with a carbon coating layer. Specifically, when preparing Li 0.95 Ni 0.45 Mn 1.54 When the positive electrode active material is O4, the carbon source is first pre-sintered in a stable gas atmosphere such as nitrogen to obtain a carbon material, and then the carbon material and Li 0.95 Ni 0.45 Mn 1.54O4 positive electrode active materials are mixed evenly and subjected to secondary sintering treatment to obtain Li 0.95 Ni 0.45 Mn 1.54 O4 positive electrode active material. The carbon source is selected from at least one of fructose, polyethylene glycol, galactose, polyvinyl pyrrolidone or tannic acid, the pre-sintering temperature is, for example, 550°C, the pre-sintering time is, for example, 5 hours, the secondary sintering temperature is, for example, 350°C, and the secondary sintering time is, for example, 12 hours.

[0041] In one embodiment of the present invention, when preparing the positive electrode, the Li 0.95 Ni 0.45 Mn 1.54 The O4 positive electrode active material, PVDF and Super P are mixed in a mass ratio of 98:1:1, dissolved in an organic solvent, and stirred under a vacuum mixer until the system is uniform to obtain a positive electrode slurry, and then the positive electrode slurry is evenly coated on an aluminum foil, and then transferred to an oven for drying after drying at room temperature, and a positive electrode sheet is obtained through cold pressing and slitting. The organic solvent is, for example, N-methylpyrrolidone (NMP).

[0042] In one embodiment of the present invention, the negative electrode plate includes, for example, a negative electrode current collector and a negative electrode active layer coated on at least one surface of the negative electrode current collector, wherein the negative electrode current collector is, for example, selected from a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foam copper current collector, or a stainless steel current collector.

[0043] In one embodiment of the present invention, the negative electrode active layer includes a negative electrode active material, a conductive agent, a thickener, and a binder. Among them, the proportion of the negative electrode active material, the conductive agent, the thickener, and the binder can be selected according to actual needs. In this embodiment, the negative electrode active material is selected from at least one of graphite, silicon, or carbon dioxide. Further, the negative electrode active material is selected from at least one of artificial graphite, natural graphite, soft carbon, hard carbon, pure silicon, silicon oxide compounds, and silicon carbon compounds.

[0044] In one embodiment of the present invention, the conductive agent is selected from at least one of SuperP, acetylene black, Ketjen black, carbon nanotubes or graphene, etc. The thickener includes, for example, carboxymethyl cellulose sodium (CMC-Na), etc. The binder is selected from at least one of PVDF, PEO, PA, polypropylene, polyacrylate, polyvinyl ether, PMMA, polyhexafluoropropylene or SBR, etc.

[0045] In one embodiment of the present invention, the negative electrode current collector is, for example, copper foil, the negative electrode active material is, for example, artificial graphite, the conductive agent is, for example, SuperP, the thickener is, for example, CMC-Na, and the binder is, for example, SBR. Specifically, the negative electrode active material, the conductive agent, the thickener, and the binder are mixed in a mass ratio of 96:1:1:2, and a deionized water solvent is added, and then the mixture is stirred and mixed evenly under the action of a vacuum mixer to obtain a negative electrode slurry, and the negative electrode slurry is coated on the copper foil, and then transferred to an oven for drying after drying at room temperature, and the negative electrode sheet is obtained through cold pressing and slitting.

[0046] In one embodiment of the present invention, the diaphragm is, for example, a conventional diaphragm, a ceramic diaphragm, a polymer diaphragm, a non-woven fabric or an inorganic-organic composite diaphragm, etc. Specifically, the diaphragm is, for example, a single-layer polypropylene (PP) film, a single-layer polyethylene (PE) film, a double-layer PP / PE film, a double-layer PP / PP film or a three-layer PP / PE / PP film, etc., wherein the thickness of the diaphragm is, for example, 9 μm-15 μm. In this embodiment, for example, a single-layer PP film with a thickness of 12 μm is selected as the diaphragm.

[0047] In one embodiment of the present invention, the positive electrode sheet, the separator and the negative electrode sheet are placed in sequence, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role. Then, the aluminum plastic film is wrapped, transferred to a vacuum oven at 120°C for drying, and the prepared lithium ion battery electrolyte is injected at 3.0g / Ah and sealed. After the electrolyte is formed, a soft-pack lithium ion battery with a capacity of 1Ah is obtained.

[0048] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.

[0049] Example 1

[0050] Preparation of positive electrode: fructose is pre-sintered in a stable gas atmosphere such as nitrogen to obtain carbon material, and then the carbon material and Li 0.95 Ni 0.45 Mn 1.54 O4 positive electrode active materials are mixed evenly and subjected to secondary sintering treatment to obtain Li 0.95 Ni 0.45 Mn 1.54 O4 positive electrode active material. Li containing carbon coating layer 0.95 Ni 0.45 Mn 1.54O4 positive electrode active material, PVDF and SuperP are mixed in a mass ratio of 98:1:1, dissolved in solvent NMP, and stirred under the action of a vacuum mixer until the system is uniform to obtain positive electrode slurry. The positive electrode slurry is then evenly coated on aluminum foil, and then transferred to an oven for drying after drying at room temperature. The positive electrode sheet is obtained through processes such as cold pressing and slitting.

[0051] Preparation of negative electrode sheets: Artificial graphite, SuperP, CMC-Na and SBR are mixed in a mass ratio of 96:1:1:2, and deionized water solvent is added, and then fully stirred and mixed under the action of a vacuum mixer to obtain negative electrode slurry, and the negative electrode slurry is coated on a copper foil, and then dried at room temperature and transferred to an oven for drying, and after processes such as rolling and cutting, the negative electrode sheet is obtained.

[0052] Preparation of electrolyte: In an argon atmosphere glove box with a moisture content of less than 10ppm, according to the composition of the electrolyte described in Table 1, battery-grade FEMC and FEC were mixed at a mass ratio of 9:1 to obtain a fluorocarbonate solvent, and then LiPF6 and compound 1 were added to the fluorocarbonate solvent and mixed to prepare a lithium-ion battery electrolyte. The contents of LiPF6 and compound 1 in the electrolyte were 13wt% and 0.5wt%, respectively.

[0053] Selection of diaphragm: A single-layer PP film with a thickness of 12 μm was selected as the diaphragm.

[0054] Preparation of the battery: The positive electrode, separator and negative electrode are placed in sequence, and wrapped with aluminum-plastic film, transferred to a vacuum oven at 120°C for drying, and then the above-prepared lithium-ion battery electrolyte is injected at 3.0 g / Ah and sealed. After the electrolyte is formed, a soft-pack lithium-ion battery with a capacity of 1 Ah is obtained.

[0055] Example 2

[0056] The mass ratio of FEMC to FEC is 8:2, and the other steps are the same as those in Example 1.

[0057] Example 3

[0058] The mass ratio of FEMC to FEC is 7:3, and the other steps are the same as those in Example 1.

[0059] Example 4

[0060] The content of compound 1 in the electrolyte is 0.1 wt %. The other steps are the same as those in Example 2.

[0061] Example 5

[0062] The content of compound 1 in the electrolyte is 1 wt %. The other steps are the same as those in Example 2.

[0063] Example 6

[0064] The electrolyte contains compound 2, and the contents of compound 1 and compound 2 in the electrolyte are 0 and 0.5 wt % respectively. The other steps are the same as those in Example 2.

[0065] Example 7

[0066] The electrolyte contains compound 3, and the contents of compound 1 and compound 3 in the electrolyte are 0 and 0.5 wt % respectively. The other steps are the same as those in Example 2.

[0067] Example 8

[0068] The electrolyte includes LiFSI, and the contents of LiPF6 and LiFSI in the electrolyte are 12.5wt% and 0.5wt% respectively. The other steps are the same as those in Example 2.

[0069] Comparative Example 1

[0070] The content of compound 1 in the electrolyte is 0, and the other steps are the same as those in Example 2.

[0071] Comparative Example 2

[0072] The electrolyte contains methyl ethyl carbonate (EMC) but no FEMC, and the mass ratio of EMC to FEC is 8:2. The other steps are the same as those in Example 2.

[0073] Comparative Example 3

[0074] The electrolyte contains an additive tris(trimethylsilyl)phosphate (TMSP), and the contents of compound 1 and TMSP in the electrolyte are 0 and 0.5 wt % respectively. The other steps are the same as those in Example 2.

[0075] The raw material component contents and raw material mass ratios required for the electrolytes prepared in the embodiments and comparative examples are shown in Table 1.

[0076] Table 1, composition of electrolyte in Examples 1-8 and Comparative Examples 1-3

[0077]

[0078]

[0079] In the present invention, performance tests were performed on lithium ion batteries prepared using different electrolyte ratios in Examples 1-8 and Comparative Examples 1-3. The test results are shown in Table 2.

[0080] In one embodiment of the present invention, for example, a direct current resistance (DCR) test is performed on a lithium-ion battery. Specifically, at 25°C, when the battery is discharged to a 50% state of charge (SOC) at a current of 1C, the voltage of the battery is detected and recorded as the initial voltage. Then the current is increased to 4C and maintained for 30s. After the battery voltage is detected to be stable, the stable voltage is recorded as the terminal voltage, and the difference between the terminal voltage and the initial voltage is calculated. The ratio of the difference to the 4C current value is the DCR of the battery.

[0081] In one embodiment of the present invention, for example, a high-temperature storage gas generation rate test is performed on a lithium-ion battery. Specifically, the battery is fully charged and placed in a 60°C constant temperature box for 15 days, and then the volume of the battery is tested, and the difference between the volume and the original volume of the battery is calculated, and the percentage value of the difference and the original volume is used as the high-temperature storage gas generation rate of the battery.

[0082] In one embodiment of the present invention, for example, a high temperature cycle stability test is performed on a lithium-ion battery. Specifically, the battery is cycled at 45°C at a charge / discharge rate of 1C / 1C within a charge / discharge cutoff voltage range of 3.4V-4.85V. The test is terminated when the battery capacity reaches 80% of the first cycle capacity State of Health (SOH), and the number of high temperature cycles of the battery is recorded.

[0083] Table 2 Performance test results of lithium ion batteries in Examples 1-8 and Comparative Examples 1-3

[0084] Group 25℃DCR(mOhm) Gas production rate at 60℃ storage (%) High temperature cycle number (80% SOH) Example 1 114.7 47 432 Example 2 108.3 38 478 Example 3 101.2 42 401 Example 4 107.3 43 437 Example 5 127.3 33 409 Example 6 118.1 41 445 Example 7 121.8 38 463 Example 8 103.8 33 474 Comparative Example 1 103.4 63 342 Comparative Example 2 160.7 75 278 Comparative Example 3 106.3 57 389

[0085] Please refer to Table 1 and Table 2. Comparative Examples 1-3 show that in the total solvent composed of FEC and FEMC, when the content of FEC in the total solvent increases from 10wt% to 20wt%, the DCR and storage gas production rate of the battery decrease, and the number of high-temperature cycles increases, indicating that FEC can enhance the conductivity of the electrolyte, and can preferentially decompose into a film at the negative electrode, enhance the interface stability, thereby reducing the impedance and high-temperature storage gas production rate of the battery, and improving the high-temperature cycle stability. When the content of FEC in the total solvent continues to increase from 20wt% to 30wt%, although the DCR of the battery decreases, the number of high-temperature cycles also decreases significantly, and the storage gas production rate increases, indicating that due to excessive decomposition of FEC, excessive interface byproducts are produced, which affects the high-temperature cycle stability and high-temperature storage gas production rate of the battery. Therefore, by controlling the mass ratio of FEC and FEMC, the impedance, high-temperature storage gas production rate and high-temperature cycle stability of the battery can be taken into account.

[0086] Please refer to Table 1 and Table 2. By comparing Example 2, Example 4 and Example 5, it can be seen that when the content of compound 1 in the electrolyte increases from 0.1wt% to 0.5wt%, although the DCR of the battery increases, the storage gas production rate decreases, and the number of high-temperature cycles increases. When the content of compound 1 in the electrolyte continues to increase from 0.5wt% to 1wt%, although the storage gas production rate of the battery decreases, the number of high-temperature cycles also decreases significantly, and the impedance increases significantly, indicating that when the content of compound 1 is too large, the excess compound 1 may be converted into a nucleophilic compound to attack the cyclic compound in the electrolyte system, and cause the polymerization of the cyclic compound 1, and the increase of interface byproducts, thereby affecting the impedance and high-temperature cycle stability of the battery. Therefore, by controlling the content of compound 1 in the electrolyte, the impedance, high-temperature storage gas production rate and high-temperature cycle stability of the battery can be taken into account.

[0087] Please refer to Table 1 and Table 2. By comparing Example 2, Example 6-7 and Comparative Example 1, it can be seen that when the electrolyte contains the first additive such as Compound 1, Compound 2 or Compound 3, although the DCR of the battery is slightly increased, the storage gas production rate is significantly reduced, and the number of high-temperature cycles is significantly increased, indicating that the first additive can inhibit the high-temperature storage gas production of the battery and improve the high-temperature cycle stability of the battery. Moreover, among the three first additives of Compound 1, Compound 2 and Compound 3, when the electrolyte contains Compound 1, the DCR and storage gas production rate of the battery are the smallest, and the number of high-temperature cycles is the largest, indicating that among Compound 1, Compound 2 and Compound 3, Compound 1 has the most obvious effect on improving the high-temperature storage gas production rate and high-temperature cycle stability of the battery.

[0088] Please refer to Table 1 and Table 2. By comparing Example 2 and Comparative Example 2, it can be seen that when the total solvent mainly contains EMC, the DCR and storage gas production rate of the battery are greater, and the number of high-temperature cycles is less, compared with the total solvent mainly containing FEMC. This shows that fluorocarbonate solvents such as FEMC can significantly improve the impedance, high-temperature storage gas production rate and high-temperature cycle stability of the battery to ensure that the battery can work normally under a high-voltage system.

[0089] Please refer to Table 1 and Table 2. Comparison of Example 2, Comparative Example 1 and Comparative Example 3 shows that in fluorocarbonate solvents, when conventional acid removal additives such as TMSP are used, the DCR of the battery increases, the storage gas production rate decreases slightly, and the number of high-temperature cycles increases slightly. However, when compound 1 is used in fluorocarbonate solvents, the storage gas production rate of the battery is significantly reduced, and the number of high-temperature cycles increases significantly, indicating that the combination of fluorocarbonate solvents and TMSP cannot effectively improve the high-temperature storage gas production rate and high-temperature cycle stability of the battery. Only when the fluorocarbonate solvent and the first additive such as compound 1 work synergistically can the high-temperature storage gas production rate and high-temperature cycle stability of the battery be comprehensively improved.

[0090] Please refer to Table 1 and Table 2. By comparing Example 2 and Example 8, it can be seen that when the electrolyte contains the second lithium salt LiFSI, the high-temperature cycle number of the battery does not change significantly, but the impedance and storage gas production rate are significantly reduced, which shows that the introduction of the second lithium salt can not only reduce the viscosity of the electrolyte, but also the sulfur-containing and fluorine-containing inorganic compounds produced by its decomposition can enhance the stability of the interface, thereby effectively reducing the impedance of the battery and the high-temperature storage gas production.

[0091] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned lithium-ion batteries, and the lithium-ion battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned lithium-ion battery, so the advantages of the above-mentioned lithium-ion battery are included, which will not be elaborated here.

[0092] In summary, the present invention provides a lithium-ion battery electrolyte and its application. By introducing a fluorocarbonate solvent into the electrolyte, the high-voltage resistance of the electrolyte can be improved, so that the electrolyte is suitable for use in high-voltage system batteries. By introducing a first additive into the electrolyte, the fluorocarbonate solvent and the first additive work synergistically to form a stable SEI film at the contact interface between the negative electrode and the electrolyte, and a stable CEI film at the contact interface between the positive electrode and the electrolyte, thereby ensuring the stability of the interface between the electrode and the electrolyte at high temperature, thereby significantly improving the high-temperature cycle stability of the battery, and inhibiting the impedance growth of the battery and the gas production during high-temperature storage.

[0093] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.

[0094] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. A lithium ion battery electrolyte, characterized in that: At least the following components are included: Fluorinated carbonate solvents, including 2,2,2-trifluoroethyl methyl carbonate and fluoroethylene carbonate; a lithium salt comprising a first lithium salt comprising lithium hexafluorophosphate; and The additive comprises a first additive, wherein the first additive has a general structural formula of: Wherein, R1 and R2 are each independently selected from a substituent having 1-6 carbon atoms, 0-4 unsaturation degrees and 0-3 heteroatoms, and the heteroatoms are selected from at least one of oxygen, nitrogen or sulfur.

2. The lithium ion battery electrolyte according to claim 1, characterized in that: The substituent is selected from at least one of an alkyl group, an alkenyl group, an alkynyl group, a carbonyl group, an ester group, an amino group or a heterocycle.

3. The lithium ion battery electrolyte according to claim 1, characterized in that The first additive is selected from At least one of .

4. The lithium ion battery electrolyte according to claim 1, characterized in that: The content of the first additive in the electrolyte is 0.05wt%-3wt%.

5. The lithium ion battery electrolyte according to claim 1, characterized in that: The content of the 2,2,2-trifluoroethyl methyl carbonate in the electrolyte is 10 wt%-85 wt%.

6. The lithium ion battery electrolyte according to claim 5, characterized in that: In the fluorocarbonate solvent, the mass ratio of the 2,2,2-trifluoroethyl methyl carbonate to the fluoroethylene carbonate is 9:1 to 7:

3.

7. The lithium ion battery electrolyte according to claim 1, characterized in that: The lithium salt further includes a second lithium salt, and the second lithium salt is selected from at least one of lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide.

8. The lithium ion battery electrolyte according to claim 7, characterized in that: The content of the lithium salt in the electrolyte is 12wt%-20wt%, and the content of the first lithium salt in the electrolyte is 8wt%-20wt%.

9. A lithium ion battery, characterized in that: include: A positive electrode sheet, comprising a positive electrode active material, wherein the positive electrode active material has a structural formula of Li a Ni x Mn y O 4-z M z , wherein 0.9≤a≤1.1, 0.4≤x≤0.6, 1.4≤y≤1.6, 0≤z≤0.1, and M is selected from at least one of Cl, Br, I, S, Se, Te or F; Negative electrode; A separator, disposed between the positive electrode sheet and the negative electrode sheet; and An electrolyte, wherein the electrolyte is selected from the lithium ion battery electrolyte according to any one of claims 1 to 8.

10. An electronic device, characterized in that: Includes the lithium ion battery as claimed in claim 9.

Citation Information

Patent Citations

  • Nonaqueous electrolyte for electrochemical device, and electrochemical device

    CN103000948A

  • Low-temperature type lithium ion battery electrolyte and lithium ion battery

    CN103107364A

  • Electrolyte for inhibiting growth of lithium dendrites and lithium-containing battery thereof

    CN112216866A

  • High-voltage-resistant lithium secondary battery electrolyte and lithium secondary battery

    CN114069047A

  • Lithium ion battery electrolyte, lithium ion battery and electrochemical equipment

    CN118676437A